Ecthyma gangrenosum: fatal form of pseudomonas aeruginosa infection in an eight-month-old infant - N. V. Rymarenko; A. V. Bobrysheva; E. A. Krjuger; E. Ya. Halilov (Журнал инфектологии)
The clinical features of the onset and dynamics of ecthyma gangrenosum caused by Pseudomonas aeruginosa with the development of sepsis are observed in an eight-monthold child. The article incudes a detailed description and corresponding photo images of skin manifestations of the disease in the form of solid hemorrhagic fast-growing papules with a cyanotic halo and developing necrosis in the centre of the elements followed by the formation of ulcers or blisters. The diagnosis was made on basis of clinical manifestations and Pseudomonas aeruginosa culture from the contents of the blisters and blood. In spite of being treated intensely and being given antibacterial preparations possessing anti-Pseudomonad activity, the girl died on the 17th day after hospitalization.